Structural Optimization of Cross-laminated Timber Panels in One-way Bending. (April 2019) - Mayencourt, Paul; Mueller, Caitlin
Abstract: In the United States, Cross-Laminated Timber (CLT) panels are gaining considerable attention as designers focus on building more ecological and sustainable cities. These panels, which are surface elements made from layers of orthogonally bonded layers of dimensional lumber, can speed up construction on site due to their high degree of prefabrication, and consequently, CLT is deployed for slab systems, walls and composite systems in modern buildings. However, the structural use of material is inefficient in CLT panels used in bending. The core of the material does not contribute much to the structural behavior and acts merely as a spacer between the outer layers. This research offers an alternative design of an optimized CLT panel with the goal of reducing material consumption and increasing the efficiency of this building component, which can help it become more ubiquitous and cost-effective in building construction. In this paper, two theoretical models for the behavior of optimized CLT panels in one-way bending action are developed, and these models are compared with physical load tests. The results demonstrate that the theoretical models accurately predict physical behavior. Furthermore, around 20% of material can be saved without major changes in the structural behavior. The reduced material consumption and cost of the proposed optimized CLT panels can help mitigate the ecological impact of the construction industry, while offering a new competitive building product to the market.